Characterization of new early-season commercial apricot cultivars in Israel and comparison to a local cultivar. Issue 1 (2nd January 2016) - Guillén, Fabian; Weksler, Asya; Lurie, Susan; Friedman, Haya
ABSTRACT: Ripening parameters of newly released apricot cultivars ("Nitzan" and "Daniel") are characterized and compared to an old local cultivar ("Mustakaui"), which is a white fleshed, sweeter, and smaller fruit, with a shorter shelf life. In 2 consecutive years, at harvest, we examined total soluble solids (TSS) and total acidity (TA) and, during postharvest, chlorophyll and firmness loss, and ethylene and carbon dioxide production rates. Our results show that "Mustakaui" is indeed sweeter and has a lower total acidity content than the other cultivars. However, "Mustakaui" has a similar rate of chlorophyll and firmness loss as the new cultivars. Despite similar rates of chlorophyll and firmness loss, "Mustakaui" produces the highest levels of carbon dioxide and "Daniel" produces the highest ethylene levels. "Nitzan", on the other hand, did not produce any ethylene in 2 consecutive years, which suggests that another ripening control mechanism exists in this cultivar. Hence, the new cultivars might harbor different ripening programs in comparison to the old "Mustakaui" cultivar. Comparing the levels of volatiles in "Mustakaui" and "Nitzan" indicates that they share the capacity to produce similar volatiles, but these are produced differently in tree-ripened or postharvest-ripened fruits. Variability in volatiles might be useful for any future breeding programs for aroma.